δ(δg)* - Sets and Functions in Topological Spaces - Bitasolo, Meriam Niepes (International Journal For Research In Mathematics And Statistics, 2019)
This study introduced the notion of delta(delta g)star set and functions in topological spaces (briefly TS). This proves that in TS, the delta-closure of a set is smaller than its delta(delta g)star- closure while the delta-interior is generally larger than its delta(delta g)star- interior. In addition, in the same space the delta(delta g)star-continuous functions, absolute-delta(delta g)star- continuous functions and rs -delta(delta g)star - continuous functions are introduced and investigated. Characterization and properties of these functions are also determined.